2019
DOI: 10.1002/lary.28433
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Comparing a Combination of Montelukast and Budesonide With Budesonide in Allergic Rhinitis

Abstract: Objectives/Hypothesis: It is not unequivocally proven whether a combination of an intranasal corticosteroids (INSs) and a cysteinyl leukotriene receptor antagonist has greater efficacy than INSs in the treatment of seasonal allergic rhinitis (SAR). Study Design: Single-center, randomized, open-label study. Methods: Study subjects included 46 participants with SAR. Participants were randomized to receive budesonide (BD; 256 μg) plus montelukast (MNT; 10 mg) (BD + MNT) or BD alone (256 μg) for 2 weeks. Visual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Finally, a total of 5 studies were included for the meta-analysis (19)(20)(21)23,24) . Characteristics of the included studies are shown in Table 1.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, a total of 5 studies were included for the meta-analysis (19)(20)(21)23,24) . Characteristics of the included studies are shown in Table 1.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…The diagnosis of AR was confirmed by skin tests or serum-specific IgE in 298 patients. Three RCTs studied paediatric and adult patients (19,20,23) while three RCTs studied only adult patients (21,22,24) . Two RCTs studied patients with seasonal AR (SAR) (19,24) , while two studied perennial AR (PAR), one with persistent disease (21,22) .…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations